Design of 2 Elements Rectangular Microstrip Patch Antenna for 2.40 GHz Using HFSS (Comprehensive Journal of Science, 2025)
In this paper, aims to design and simulate a rectangular microstrip patch antenna with a two-element array operating at 2.4 GHz using HFSS software. Microstrip patch antennas are essential components in wireless communication systems, known for their small size and high efficiency but suffer from limited bandwidth and low gain. The study focuses on improving the antenna’s performance by converting it into a two-element array to enhance gain and improve radiation patterns.The antenna design was simulated using HFSS software, evaluating key parameters such as radiation patterns, gain, and return loss. The results showed that the two-element array provides significant improvements over a single patch antenna, particularly in terms of gain and radiation efficiency. The research recommends future studies on larger array designs or different feeding techniques for further performance enhancement..
Keywords: High Frequency Structure Simulator (HFSS), The Internet of Things (IOT) The Industrial, Scientific and Medical (ISM)